2014
DOI: 10.1080/02626667.2013.877139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streamflow reductions on aquatic macroinvertebrates: linking groundwater withdrawals and assemblage response in southern New Jersey streams, USA

Abstract: A comprehensive hydro-ecological investigation was conducted to determine the ecological response of increased groundwater withdrawals from the Kirkwood-Cohansey aquifer system, an important source of water supply in southern New Jersey, USA. Collocated observations were made of aquatic-macroinvertebrate assemblages and stream hydrologic attributes to develop flow-ecology response relations. A sub-regional transient groundwater flow model (MODFLOW) was used to simulate three plausible high-stress groundwater-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…A number of studies have explored ecosystem responses to a suite of flow indices based around the five facets of the natural flow regime (e.g., Monk et al, ; Belmar et al, ; Kennen et al, ). While there is increasing recognition that fluvial ecosystems respond to comparable forms of stream temperature variability (Olden & Naiman, ), few studies have explored the ecological implications of this, and even less have examined biotic responses to flow and stream temperature variability together (a notable exception being Jackson et al, ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A number of studies have explored ecosystem responses to a suite of flow indices based around the five facets of the natural flow regime (e.g., Monk et al, ; Belmar et al, ; Kennen et al, ). While there is increasing recognition that fluvial ecosystems respond to comparable forms of stream temperature variability (Olden & Naiman, ), few studies have explored the ecological implications of this, and even less have examined biotic responses to flow and stream temperature variability together (a notable exception being Jackson et al, ).…”
Section: Discussionsupporting
confidence: 69%
“…Such frameworks have underpinned the identification and examination of over 200 "ecologically relevant" flow indices (Olden & Poff, 2003;Monk, Wood, Hannah, & Wilson, 2007) that have been related to ecological responses in lotic environments across a wide range of studies (e.g., Englund & Malmqvist, 1996;Clausen & Biggs, 1997;Monk et al, 2006;Kennen, Riva-Murray, & Beaulieu, 2010;Belmar et al, 2013;Worrall et al, 2014). Such ecohydrological relationships have also been established to quantify the biotic alterations driven by different forms of hydrological modification, including river impoundments (Armanini et al, 2014) and groundwater abstraction (Kennen, Riskin, & Charles, 2014).…”
mentioning
confidence: 99%
“…However, land use changes (Chadwick et al., ; López‐Moreno et al., ) and water resource management practices have profoundly altered river flow regimes (De Graaf, Van Beek, Wada, & Bierkens, ; Gleeson & Richter, ; Lehner et al., ), significantly threatening the integrity of lotic ecosystems globally (Bunn & Arthington, ; Poff et al., ; Vörösmarty et al., ). For example, groundwater abstraction substantially reduces river discharges worldwide (De Graaf et al., ) and profoundly alters lotic ecosystems (Bradley, Streetly, Farren, Cadman, & Banham, ; Bradley et al., ; Kennen, Riskin, & Charles, ). Conversely, some management activities elevate river discharges (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aldous and Bach (2014) found that, for fens in Oregon, USA, water table depth is the critical issue rather than river flow, with a required water table within 35 cm of the surface. Hendriks et al (2014) reported that drainage and groundwater abstraction in sandy catchments in the Netherlands meant that low flows were reduced below the environmental flow criterion, whilst Kennen et al (2014) found that groundwater abstraction led to a 20% reduction in intolerant macro-invertebrates in New Jersey, USA, due to reduced river flow. Streetly et al (2014), working in the midlands of England, also found that flow reductions caused by The changing role of ecohydrological science in guiding environmental flowsgroundwater abstraction altered ecological conditions (as measured by relevant biotic indices).…”
Section: Historical Contextmentioning
confidence: 99%
“…The science of environmental flows has also benefited from closer links with other aspects of hydrological science. For example, groundwater modelling assists with understanding groundwater-fed ecosystems (Kennen et al 2014, Streetly et al 2014 including those in permeable sandy substrata (Hendriks et al 2014).…”
Section: State Of the Sciencementioning
confidence: 99%